Drought resistance in rubber tree 1. Water balance and primary production in six clones subjected to water deficit - Conceição, Heraclito E. Oliveira da; Oliva, Marco Antonio; Lopes, Nei Fernandes; Neto, Olinto Gomes da Rocha (Pesquisa Agropecuaria Brasileira, 2014)
Plants from IAN 717, IAN 873, IAN 2903, IAN 3087, IAN 6323 and Fx 3899 rubber tree (Hevea spp) clones grown in greenhouse were subjected to increasing soil water deficits, in order to evaluate the effects of water deficit on leaf water potential, stomatal resistance, photosynthesis, transpiration and chlorophyll content. Decreases in soil water potential reduced linearly and differentially the leaf water potential for all clones. The highest reduction values were found in IAN 717, IAN 3087 and IAN 873, and the lowest one in IAN 6323. Leaf water potential between -1.6 and -2.0 MPa caused a fast increase in stomatal resistance and a sharp reduction in transpiration rates for all clones. The lowest stomatal resistance volumes and the highest reductions in transpiration were in the IAN 6323. The highest water compensation point was -2,35 MPa from IAN 2903 and Fx 3899 progenies and the lowest was-3,18 MPa in the IAN 6323 progeny. IAN 6323 clone showed an efficient mechanism of drought avoidance and an effective stability of the photosynthesis apparatus under stress conditions. To a lesser degree, the IAN 717 and the IAN 3087 were resistant too.